Advancing Management Strategies with AI and IoT for Operational Excellence and Competitive Edge - Zulkarnain, Andy; Zainum Ikhsan, Ramzi; Septiani, Nanda; Victorianda (Pandawan, 2025)
As organizations face increasing competition and technological advancements, optimizing operations and managing resources efficiently is crucial for maintaining a competitive edge. The integration of emerging technologies like Artificial Intelligence (AI) and the Internet of Things (IoT) enhances efficiency, improves resource allocation, and drives growth. This study explores how AI and IoT adoption optimizes business processes, improves decision-making, and fosters a competitive advantage Using a quantitative approach, data from 200 executives in AI and IoT-implemented industries were analyzed. The analysis, conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), indicates that AI and IoT significantly enhance efficiency, resource utilization, and overall performance. Real-time monitoring and predictive analytics improve market alignment and operational trends The findings suggest that organizations adopting AI and IoT can better navigate dynamic business environments, enhance productivity, and sustain growth. Moreover, fostering innovation and continuous technological improvement is essential. This research underscores AI and IoT’s transformative potential in reshaping business operations and securing a competitive edge. Future research should explore these technologies' industry-specific impacts and broader innovation potential.